Improving Cosmetic Safety Awareness Through an Educational Program and Hands-On Workshop on a Pomegranate-Based Peel-Off Mask for Adolescents - Putriana Rachmawati; Lusy Noviani; Sharon Susanto; Yulius Evan Christian; Madeleine Rose Karjono; Sherly Nataya; Hellery Yovanti Joseph; Revista Noveria (LP2M INSURI Ponorogo, 2026)
Adolescents are increasingly exposed to cosmetic products and marketing claims, yet their awareness of cosmetic safety remains limited. Interactive educational approaches that combine theoretical knowledge with practical experience are still rarely implemented. This study aimed to evaluate the effectiveness of an interactive educational intervention in improving adolescents’ knowledge of cosmetic safety and the appropriate use of skincare ingredients. A quasi-experimental study with a one-group pretest–posttest design was conducted on December 3, 2025, involving n = 61 high school students. The intervention integrated BPOM-based education with a hands-on workshop on peel-off mask formulation. Knowledge was assessed using a 10-item questionnaire, which was pilot-tested for clarity and relevance. Data were analyzed using a paired t-test (p < 0.05). The mean knowledge score increased from 72.71±16.72 to 84.67±10.45, with a statistically significant difference (p = 0.002) and a large effect size (Cohen’s d = 1.36). The distribution of scores shifted toward higher categories, indicating improved understanding. Participants also reported high levels of satisfaction with the program. The intervention effectively improved adolescents’ knowledge of cosmetic safety. The novelty lies in integrating regulatory education with hands-on formulation activities as an interactive learning model. However, the absence of a control group and the single-setting design limit generalizability.